2018
DOI: 10.12659/msm.912071
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Study of the Incidence, Risk Factors, and Prognostic Factors Associated with Bone Metastases in Women with Uterine Cervical Cancer Using Surveillance, Epidemiology, and End Results (SEER) Data Analysis

Abstract: BackgroundThe aims of this study were to investigate the incidence and risk factors for the development of bone metastases and prognosis in women with cancer of the uterine cervix using database analysis.Material/MethodsThe National Cancer Institute (NCI) Surveillance, Epidemiology, and End Results (SEER) database was analyzed for the incidence and survival rates of women diagnosed with uterine cervical cancer in the United States between 2010–2015. Multivariate logistic regression analysis identified risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 26 publications
2
25
0
2
Order By: Relevance
“…Previous studies had shown that lung metastases can signi cantly worsen the prognosis of patients. 19 .The median survival time for diagnosis of distant disease is 12 months 4 In this study, the 3-year and 5-year survival rates for 411 patients with newly diagnosed lung metastases were 33.8% and 22.8%, respectively, similar to other studies 20 21 .It was found that primary site surgery treatment and chemotherapy can improve overall survival. Therefore, for patients with ovarian cancer with lung metastases, active surgery and chemotherapy are encouraged.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies had shown that lung metastases can signi cantly worsen the prognosis of patients. 19 .The median survival time for diagnosis of distant disease is 12 months 4 In this study, the 3-year and 5-year survival rates for 411 patients with newly diagnosed lung metastases were 33.8% and 22.8%, respectively, similar to other studies 20 21 .It was found that primary site surgery treatment and chemotherapy can improve overall survival. Therefore, for patients with ovarian cancer with lung metastases, active surgery and chemotherapy are encouraged.…”
Section: Discussionsupporting
confidence: 83%
“…Such distant metastases were further reported in the studies with the limited samples [7,8]. Bone metastases [9,10] and lung metastases [11] were also descripted based on the relatively large population. As to the effect of distant metastases on the survival of patients, around 13% of UCC patients were diagnosed at an advanced stage, leading to the decreased survival [12].…”
Section: Ivyspringmentioning
confidence: 77%
“…Bone metastasis rarely occurs in cervical cancer, with an incidence of 0.8‒2.3%. 6 , 15 , 16 Among them, spinal metastasis is the most common (36.36%). 16 Bone metastases from ovarian malignant tumors are rare in the clinic, and reports show that the incidence of ovarian cancer bone metastases is only 0.1‒0.6%.…”
Section: Discussionmentioning
confidence: 99%